Absence of Posterior Vitreous Detachment Is a Risk Factor of Severe Bleb-Related Endophthalmitis. (14th January 2019) - Umazume, Kazuhiko; Suzuki, Jun; Usui, Yoshihiko; Maruyama, Katsuhiko; Wakabayashi, Yoshihiro; Goto, Hiroshi
Abstract : Purpose . Bleb-related endophthalmitis (BRE) after glaucoma surgery is an infection caused by bacteria in the avascular bleb gaining access into the eye. We report the clinical features and outcome of 10 consecutive eyes with severe BRE treated at our hospital. Methods . Ten patients (10 eyes) with stage IIIb BRE after trabeculectomy diagnosed and treated at the Department of Ophthalmology, Tokyo Medical University, between April 2013 and May 2015, were studied. Patient background, type of glaucoma, interval from the first trabeculectomy, pretreatment bleb findings, causative microorganisms, surgical methods, status of posterior vitreous detachment (PVD), and postoperative visual acuity were examined. Results . The 10 patients comprised 8 males and 2 females, with mean age of 70.6 years at BRE onset. The types of glaucoma were open-angle glaucoma in 7 patients, neovascular glaucoma in 2, and secondary glaucoma in 1. All eyes underwent trabeculectomy combined with mitomycin C prior to the development of BRE. The interval from the first glaucoma surgery to onset of endophthalmitis was 8.5 ± 4.1 years. Examination of the bleb revealed leakage of aqueous humor from the avascular bleb in all eyes. Bacteria were isolated from intraocular samples of 8 eyes; namely, Viridans streptococci in 5 eyes, Staphylococcus epidermidis in 1, Branhamella catarrhalis in 1, and coagulase-negative Staphylococci in 1. BRE was treated by vitrectomy in 9 eyes and enucleation in 1 eye. PVD was produced intentionally during vitrectomy in 6 eyes. Histopathological examination of the enucleated eye showed no PVD. Visual acuity improved by 3 lines or more in 6 patients, while decimal visual acuity remained lower than 0.1 in 4 patients. Conclusion . BRE developed frequently in eyes with no PVD. The absence of PVD may be a risk factor of severe BRE.